Pedunculopontine nucleus stimulation induces monocular oscillopsia. Issue 2 (16th January 2009) - Ferraye, M U; Gerardin, P; Debû, B; Chabardès, S; Fraix, V; Seigneuret, E; LeBas, J-F; Benabid, A-L; Tilikete, C; Pollak, P
Abstract : Two patients with Parkinson's disease with pedunculopontine nucleus (PPN) stimulation for gait impairments reported "trembling vision" during the setting of the electrical parameters, although there was no clinically observable abnormal eye movement. Oculomotor recordings revealed frequency locked voltage dependent vertical or oblique movements of the eye ipsilateral to the active contact, suggesting current spreading to the mesencephalic oculomotor fibres. These results emphasise the difficulty of stimulating this mesencephalic region.